Kepemimpinan Perempuan dalam Entrepreneur - Andi Mardiana (Al-Ulum, 2020)
Abstract This study analyzes women's leadership in order to find out how women's leadership in the world of entrepreneurship. The results showed that women always prioritized interpersonal relations, communication, workers' motivation, task-oriented, and more oriented to comparison with men who were more concerned with aspects of strategic design and analysis. A leader today is not only from men, but women are also able to become leaders. In contrast to ancient times, now women are not just homemakers and no longer dominate under men. The concept of gender equality can be accepted by society: women and men as equals.